Predictive mathematical modeling for EC50 calculation of antioxidant activity and antibacterial ability of Thai bee products - Rungsiri Suriyatem, Rafael A. Auras, Pilairuk Intipunya, Pornchai Rachtanapun (Journal of Applied Pharmaceutical Science, 2017)
Antioxidant activities of bee products from Thailand (honey, bee pollen and propolis) via the 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2,2’-azinobis-(3-ethylbenzothiazoline-6-sulphonate) (ABTS) assays were determined. The prediction of the EC50 (the half maximal effective concentration) were studied using the logistic, sigmoidal, dose response, and asymmetric 5 parameters (5P) regression models. The antimicrobial ability was tested against Staphylococcus aureus (TISTR 517), Bacillus cereus (TISTR 687), and Escherichia coli (TISTR 1261). Propolis extract with higher total phenolic content (TPC) exhibited more effective antiradical action against the DPPH and ABTS, followed by bee pollen extract and honey. All four regression models could be used to estimate the EC50 of the bee products. However, the dose-respond and 5P provide the better EC50 prediction for the bee products than the others based on the comparability of their results to those of right-angled triangle method. Thai bee products had effective antimicrobial activities on each test microorganism. The antimicrobial potency of the bee products was ranged in the order: propolis> bee pollen >honey. Results revealed that antioxidant activity and antimicrobial ability of the bee products correlated with the TPC values.
Keywords: EC50 prediction, honey, phenolic compounds, pollen, propolis.